2000
DOI: 10.1046/j.1365-2273.2000.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Uvulopalatopharyngoplasty versus laser assisted uvulopalatoplasty for the treatment of snoring: an objective randomised clinical trial

Abstract: This study was designed to evaluate objectively the clinical effectiveness of surgery for snoring and to compare the results of conventional uvulopalatopharyngoplasty (UPPP) and laser assisted uvulopalatoplasty (LAUP) in the treatment of snoring. Patients who had been referred for investigation and treatment of their snoring were randomly allocated to receive either UPPP or LAUP. Forty-seven patients with confirmed palatal flutter had surgery and all of them had a preoperative and postoperative objective asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
(50 reference statements)
1
24
0
1
Order By: Relevance
“…Benefits of LAUP for snoring have been evaluated in earlier studies [3][4][5][15][16][17][18][19][20][21]. These studies showed subjective improvement in snoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benefits of LAUP for snoring have been evaluated in earlier studies [3][4][5][15][16][17][18][19][20][21]. These studies showed subjective improvement in snoring.…”
Section: Discussionmentioning
confidence: 99%
“…It goes without saying that objective snoring recordings have to be reliable. Some studies have shown objective reductions in snoring after LAUP [3,5], while others have not [4]. This raises the question of whether snoring recordings are reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is risk of developing postoperative short-or long-term velopharyngeal insuffi ciency [15] . Osman et al [4] found a success rate of 89.9% in the postoperative period and this rate declined to 83.3% in the long-term. In our study, the postoperative success rate was 83% in UPPP patients.…”
Section: Discussionmentioning
confidence: 97%
“…Insuffi cient dilation of the upper respiratory tract muscles during sleep may result in snoring [3] . The soft palate is the most common site obstruction during snoring; however, the nose, epiglottis, tongue base, tonsils, and other regions of the upper airway tract may cause snoring [4] . Several surgical methods have been described for treatment.…”
Section: Introductionmentioning
confidence: 99%